Steel welded parts

By forming a specific zinc-based coating structure on the surface of the steel, the zinc liquid metal diffuses into the grains during the spot welding process, solving the problem of insufficient crack resistance of LME at the steel welding points in the prior art, and achieving high-strength and corrosion-resistant welding effects.

JP7656232B2Active Publication Date: 2025-04-03NIPPON STEEL CORPORATION
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023551930
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-10-01
Filing Date
2022-09-30
Publication Date
2025-04-03
Estimated Expiration
2042-09-30

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve the crack resistance of liquid metal embedding (LME) at steel welding points, especially at spot welding of high-strength zinc-based coated steel.

Method used

By forming a specific zinc-based coating structure on the surface of the steel, the zinc-based coating diffuses the zinc-based coating into the grain during spot welding, so that its depth exceeds the depth of the internal oxide layer, thereby preventing the accumulation of zinc-liquid metals at the grain boundaries.

Benefits of technology

The LME crack resistance in the spot welding area is significantly improved, ensuring the high strength and corrosion resistance of steel welded parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007656232000003
    Figure 0007656232000003
  • Figure 0007656232000004
    Figure 0007656232000004
  • Figure 0007656232000005
    Figure 0007656232000005
Patent Text Reader

Abstract

Provided is a steel welded member that has a high resistance to LME of a spot welded section. In this steel welded member, a plurality of Zn-plated steel materials each having a Zn-based plating layer on the surface of a steel material have been joined via at least one spot welded section. The steel welded member is characterized in that at least one of the Zn-plated steel materials has a tensile strength of 780 MPa or greater, said steel material has a component composition including, by mass%, 0.05-0.40% C, 0.2-3.0% Si, 0.1-5.0% Mn, and 0.4-1.50% sol. Al, or similar, the remainder consisting of Fe and unavoidable impurities, and in a region that is 10-300 μm from an end section of a pressure welded section of the spot welded section, the difference that results from subtracting the depth of an internal oxidation layer formed in the steel material from the Zn penetration depth to which Zn from the Zn-based plating layer has penetrated into the steel material is within the range 0.1-10.0 μm.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a steel welded component, and more particularly to a steel welded component having high LME resistance of spot welds. [Background technology]

[0002] In recent years, efforts have been made to increase the strength of steel sheets used in various fields such as automobiles and building materials. For example, in the automobile field, the use of high-strength steel sheets has been increasing in order to reduce the weight of vehicle bodies in order to improve fuel efficiency. Such high-strength steel sheets typically contain elements such as C, Si, and Mn to improve the strength of the steel.

[0003] Generally, such high-strength steel sheets are required to have high corrosion resistance in order to ensure strength and design, particularly when used outdoors. As a steel sheet with improved corrosion resistance, a Zn-based plated steel sheet having a Zn-based plated layer (e.g., a Zn-Al plated layer, a Zn-Al-Mg plated layer, etc.) formed on a steel sheet is known.

[0004] For example, automotive components made of Zn-based plated steel sheets are usually assembled by welding (e.g., spot welding) after forming by pressing or the like. Therefore, in such components in which multiple plated steel sheets are joined via welds, not only the corrosion resistance of the plated steel sheets themselves but also the LME resistance of the welds (e.g., spot welds) are required. In general, it is known that welds have inferior corrosion resistance compared to sound parts that are not welded.

[0005] In relation to this, Patent Document 1 discloses a welding method capable of forming a high-quality spot-welded joint by suppressing LME by continuing to hold the welding electrode under pressure even after welding current has been stopped (extending the holding time after welding). Patent Document 2 discloses a method for improving the corrosion resistance, tensile strength, and fatigue strength of a joint in which high-strength plated steel sheets are spot-welded, characterized in that ultrasonic impact treatment is performed on the nugget part and the crack-initiating part of the heat-affected zone around it from one or both sides of the spot weld. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2017-047475 A [Patent Document 2] JP 2005-103608 A Summary of the Invention [Problem to be solved by the invention]

[0007] High-strength plated steel sheets are used in a variety of fields, including automotive components, home appliances, and building materials. When welding a plated steel sheet with a Zn-based plating layer on a high-strength steel sheet, the plated steel sheet is processed at high temperatures (e.g., about 900°C), and the Zn contained in the plating layer may be in a molten state during processing. In this case, the molten Zn may penetrate into the steel sheet and cause cracks inside the steel sheet. This phenomenon is called liquid metal embrittlement (LME), and it is known that the fatigue properties of the steel sheet are reduced due to the LME. Therefore, in order to prevent LME cracking, it is effective to suppress the penetration of Zn and other elements contained in the plating layer into the steel sheet.

[0008] Although Patent Document 1 examines the relationship between welding residual stress and penetration of molten metal, it does not examine at all the metal structure for improving the LME resistance of spot welds. Moreover, the invention described in Patent Document 2 improves corrosion resistance by repairing cracks that have occurred in spot welds etc. by applying ultrasonic impact treatment to prevent moisture from penetrating the cracks, and therefore Patent Document 2 does not necessarily fully examine the improvement of LME resistance of spot welds in an as-welded state.

[0009] In view of the above circumstances, an object of the present invention is to provide a steel welded component having high LME resistance at spot welds. [Means for solving the problem]

[0010] The inventors have discovered that, in order to solve the above-mentioned problems, it is important to improve LME resistance by diffusing molten metal such as Zn into crystal grains in the structure near the ends of the pressure welded parts of spot welds, thereby relatively suppressing the penetration and accumulation of molten metal such as Zn into the grain boundaries, and that when Zn-based plated steel having a steel structure containing crystal grains into which molten metal such as Zn easily diffuses is welded, the depth of diffusion (penetration) of Zn into the steel (inside the crystal grains) is deeper than the depth of the internal oxide layer formed in the steel. They have also discovered that the LME resistance of spot welds of such plated steel can be greatly improved by using the Zn-based plated steel defined by the present invention.

[0011] The present invention has been made based on the above findings, and the gist of the present invention is as follows. (1) A steel welded component in which a plurality of Zn-based plated steel materials having a Zn-based plated layer on a surface of the steel material are joined via at least one spot weld, At least one of the Zn-based plated steel materials has a tensile strength of 780 MPa or more, The steel material comprises, in mass%, C: 0.05-0.40%, Si: 0.2-3.0%, Mn: 0.1-5.0%, sol.Al: 0.4-1.50%, P:0.0300% or less, S: 0.0300% or less, N: 0.0100% or less, B: 0~0.010%, Ti: 0 to 0.150%, Nb: 0 to 0.150%, V: 0~0.150%, Cr: 0-2.00%, Ni: 0-2.00%, Cu: 0-2.00%, Mo: 0-1.00%, W: 0 to 1.00%, Ca: 0-0.100%, Mg: 0~0.100%, Zr: 0 to 0.100%, Hf: 0 to 0.100%, and REM: 0 to 0.100%, with the balance being Fe and impurities; A steel welded member, characterized in that in a region 10 to 300 μm from an end of a pressure welded portion of the spot weld, a difference between a penetration depth of Zn from the Zn-based plating layer into the steel material and a depth of an internal oxide layer formed in the steel material is within a range of 0.1 to 10.0 μm. (2) The welded steel member according to (1), wherein the difference is within a range of 1.5 to 10.0 μm. (3) In a region of more than 1000 μm from the end of the pressure welded portion of the spot weld, The steel welded member according to (1) or (2), wherein the Zn-based plating layer has a composition, in mass %, of Al: 0.3 to 1.5%, with the balance being Zn and impurities. (4) In a region of more than 1000 μm from the end of the pressure welded portion of the spot weld, The steel welded member according to (1) or (2), wherein the Zn-based plating layer has a composition, in mass %, of Al: 0 to less than 0.1%, with the balance being Zn and impurities. Effect of the Invention

[0012] According to the present invention, in a steel welded component obtained by spot welding a plurality of Zn-based plated steel materials, the difference between the Zn penetration depth of Zn from the Zn-based plated layer into the steel material and the depth of the internal oxide layer formed in the steel material in a region 10 to 300 μm from the end of the pressure welded portion of the spot weld is within the range of 0.1 to 10.0 μm, so that a steel welded component can be provided in which the LME resistance of the spot welded portion is greatly improved. As a result, it is possible to provide a component, particularly an automotive component, with excellent LME resistance as a whole. [Brief description of the drawings]

[0013] [Figure 1] FIG. 1 is a cross-sectional view for explaining a spot weld of an exemplary steel welded component according to the present invention. [Diagram 2] FIG. 2 is a diagram for explaining the end and the area near the end of the pressure-welded portion of an exemplary steel welded member according to the present invention, and is an enlarged view of the dashed line portion in FIG. [Diagram 3] FIG. 3 is a photograph of a cross section of an exemplary steel plate according to the present invention. [Figure 4] FIG. 4 is a schematic diagram of a cross section (internal oxidation layer) of an exemplary steel sheet according to the present invention. [Diagram 5] FIG. 5 is a schematic diagram illustrating the relationship between the Zn penetration depth and the depth of the internal oxide layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] <Steel welded components> The steel welded member according to the present invention is a steel welded member in which a plurality of Zn-based plated steel materials having a Zn-based plated layer on a surface of the steel material are joined via at least one spot weld, At least one of the Zn-based plated steel materials has a tensile strength of 780 MPa or more, The steel material (the at least one Zn-based plated steel material) is, in mass%, C: 0.05-0.40%, Si: 0.2-3.0%, Mn: 0.1-5.0%, sol.Al: 0.4-1.50%, P:0.0300% or less, S: 0.0300% or less, N: 0.0100% or less, B: 0~0.010%, Ti: 0 to 0.150%, Nb: 0 to 0.150%, V: 0~0.150%, Cr: 0-2.00%, Ni: 0-2.00%, Cu: 0-2.00%, Mo: 0-1.00%, W: 0 to 1.00%, Ca: 0-0.100%, Mg: 0~0.100%, Zr: 0 to 0.100%, Hf: 0 to 0.100%, and REM: 0 to 0.100%, with the balance being Fe and impurities; The present invention is characterized in that in a region 10 to 300 μm from an end of the pressure welded portion of the spot weld, the difference between the Zn penetration depth of Zn from the Zn-based plating layer into the steel material minus the depth of an internal oxide layer formed in the steel material is within a range of 0.1 to 10.0 μm.

[0015] In recent years, for example, weight reduction is required for automobile components to improve fuel efficiency, and so-called high-strength steel sheets (for example, tensile strength of 440 MPa or more) are used in automobile components to achieve weight reduction. Such high-strength steel sheets, particularly high-strength steel sheets used outdoors, are required to have high corrosion resistance from the viewpoint of ensuring strength and design. In recent years, Zn-plated steel sheets, in which Zn-based plating is formed on a steel sheet, have been widely used as high-strength steel sheets with excellent corrosion resistance. On the other hand, automobile components are usually assembled into a desired component shape by welding (for example, spot welding) after forming the above-mentioned plated steel sheets by press processing or the like. Therefore, since automobile components include spot welds between plated steel materials, they are required to have high LME resistance not only in the plated steel sheet but also in the vicinity of the spot welds. On the other hand, the spot welds are more likely to allow Zn from the Zn-based plating layer to penetrate into the steel sheet than healthy parts that are not welded. Therefore, the penetration of Zn progresses near the spot welds, making it easier for LME to occur, and there are cases in which the desired characteristics (particularly characteristics related to strength) of automobile components cannot be guaranteed. As will be described later, LME resistance is generally evaluated based on the presence or absence of LME cracks after welding and their length. (The longer the crack, the lower the LME resistance.) Therefore, strength itself cannot be evaluated based on LME resistance alone. Therefore, the prerequisite is that the plated steel sheet itself before welding has a certain strength.

[0016] The present inventors have therefore conducted detailed studies on a method for improving the LME resistance in the vicinity of a spot weld, and have found that the LME resistance of a spot weld can be significantly improved compared to the case of using a conventional plated steel by performing a specific grinding process as a pre-annealing process on a steel material having a specified chemical composition, performing an annealing process under specified conditions, forming a Zn-based plating layer on the obtained steel material to obtain a Zn-based plated steel material, and spot welding the Zn-based plated steel material to produce a steel welded member. A detailed analysis of the end of the pressure welded portion of the spot weld of the steel welded member thus produced revealed that in a region 10 to 300 μm from the end, the difference obtained by subtracting the depth of the internal oxide layer formed on the steel material from the Zn penetration depth of the Zn from the Zn-based plating layer into the steel material was within the range of 0.1 to 10.0 μm. Therefore, it was found that by making the penetration depth of Zn from the Zn-based plating layer into the steel material near the end of the pressure weld greater (deeper) by a predetermined distance than the depth of the internal oxide layer, the LME resistance near the spot weld is greatly improved compared to steel welded components made using conventional plated steel. Although not wishing to be bound by a particular theory, the following is considered to be the reason for the improvement in LME resistance of the spot weld. Generally, an internal oxide layer containing granular internal oxides is formed in the surface layer of the steel material. Making the diffusion (penetration) depth of Zn in the steel material surface layer deeper than the depth of the internal oxide layer formed in the steel material surface layer is achieved by diffusing molten metal such as Zn into the crystal grains that constitute the structure of the steel material surface layer. In this case, the penetration of molten metal such as Zn into the grain boundaries is relatively suppressed. It is said that one of the causes of LME is that cracks occur from Zn that has penetrated into the grain boundaries, so LME resistance is improved by diffusing molten metal such as Zn into the crystal grains and suppressing diffusion to the crystal grain boundaries. In other words, when the plated steel material defined in the present invention is spot welded, the molten metal such as Zn diffuses into the crystal grains and diffusion into the grain boundaries is suppressed, greatly improving the LME resistance in the vicinity of the spot weld. Furthermore, when the penetration depth of Zn or the like into the steel material is deeper than the depth of the internal oxide layer, it can be considered that the molten metal such as Zn diffuses into the crystal grains.Therefore, the present inventors have developed a steel welded component having high LME resistance in spot welds, which is extremely advantageous, particularly in automotive components.

[0017] The steel welded member according to the present invention will be described in detail below. The steel welded member according to the present invention is a member in which a plurality of Zn-based plated steel materials having a Zn-based plated layer on the surface of the steel material (e.g., steel plate) are joined via at least one spot weld. Thus, the steel welded member is formed by combining a plurality of Zn-based plated steel materials (i.e., two or more) by spot welding, and the Zn-based plated steel materials have a steel material and a Zn-based plated layer formed on the steel material. Another layer (e.g., a Ni plated layer, etc.) may be included between the steel material and the plated layer. The steel welded member according to the present invention includes at least one spot weld between the Zn-based plated steel materials, and may include two or more spot welds. The Zn-based plated layer may be formed on one side or both sides of the steel material. However, in order to obtain the steel welded member according to the present invention, at least one of the two Zn-based plated steel materials to be spot welded has a surface having a Zn-based plated layer as a spot welded joint surface. Furthermore, in order to obtain the steel welded member according to the present invention, at least one of the Zn-based plated steel materials has a tensile strength of 780 MPa or more and a specific component composition. In this case, the steel material can achieve high LME resistance at the welded portion. Naturally, if the mating material to be welded is a steel material of the same quality as the at least one Zn-based plated steel material, high LME resistance can also be achieved at the welded portion of the mating material. FIG. 1 shows a cross section of a spot weld of an exemplary steel welded member 1 according to the present invention. The steel welded member 1 is formed by joining two Zn-based plated steel materials 11 via a spot weld 21. The spot weld 21 is typically composed of a nugget portion 23 and a pressure weld portion 25.

[0018] [Tensile strength] At least one of the Zn-based plated steel materials according to the present invention preferably has high strength, specifically, a tensile strength of 780 MPa or more. For example, the tensile strength may be 780 MPa or more, 800 MPa or more, or 900 MPa or more. The upper limit of the tensile strength is not particularly limited, but may be, for example, 2000 MPa or less from the viewpoint of ensuring toughness. The tensile strength may be measured by taking a JIS No. 5 tensile test piece and measuring it in accordance with JIS Z 2241 (2011). The longitudinal direction of the tensile test piece is not particularly limited, and may be perpendicular to the rolling direction.

[0019] [Steel] Hereinafter, the steel material of at least one of the Zn-based plated steel materials in the present invention will be described in detail. The shape of the steel material is not particularly limited, but is preferably a steel sheet. When the steel material in the present invention is a steel sheet, the thickness is not particularly limited, but may be, for example, 0.1 to 3.2 mm.

[0020] (Steel composition) The composition of the components contained in at least one of the Zn-based plated steel materials in the present invention will be described. Unless otherwise specified, "%" regarding the content of an element means "mass%". In the numerical range of the composition, a numerical range expressed using "to" means a range including the numerical values ​​written before and after "to" as the lower and upper limits, unless otherwise specified.

[0021] (C: 0.05~0.40%) C (carbon) is an important element for ensuring the strength of steel. If the C content is insufficient, sufficient strength may not be ensured. Furthermore, if the C content is insufficient, the preferable form of fine internal oxides in the fine ferrite phase may not be obtained. Therefore, the C content is 0.05% or more, preferably 0.07% or more, more preferably 0.10% or more, and even more preferably 0.12% or more. On the other hand, if the C content is excessive, the weldability may decrease. Therefore, the C content is 0.40% or less, preferably 0.35% or less, and more preferably 0.30% or less.

[0022] (Si: 0.2 to 3.0%) Si (silicon) is an element effective in improving the strength of steel. If the Si content is insufficient, sufficient strength may not be ensured. Furthermore, Si forms oxides together with Mn, functions as pinning particles, and contributes to the refinement of the ferrite phase. In other words, if the Si content is insufficient, the preferable fine ferrite phase and the fine internal oxides in the ferrite phase may not be sufficiently generated near the surface layer of the steel sheet. Therefore, the Si content is 0.2% or more, preferably 0.3% or more, more preferably 0.5% or more, and even more preferably 1.0% or more. On the other hand, if the Si content is excessive, it may cause deterioration of the surface properties and may also promote the growth of external oxidation. Therefore, the Si content is 3.0% or less, preferably 2.5% or less, and more preferably 2.0% or less.

[0023] (Mn: 0.1-5.0%) Mn (manganese) is an element effective in improving the strength of steel by obtaining a hard structure. If the Mn content is insufficient, sufficient strength may not be ensured. Furthermore, Mn forms oxides with Si, functions as pinning particles, and contributes to the refinement of the ferrite phase. In other words, if Mn is insufficient, the preferable fine ferrite phase and the fine internal oxides in the ferrite phase may not be sufficiently generated near the surface layer of the steel sheet. Therefore, the Mn content is 0.1% or more, preferably 0.5% or more, more preferably 1.0% or more, and even more preferably 1.5% or more. On the other hand, if the Mn content is excessive, the metal structure may become non-uniform due to Mn segregation, which may reduce workability and may promote external oxidation growth. Therefore, the Mn content is 5.0% or less, preferably 4.5% or less, more preferably 4.0% or less, and even more preferably 3.5% or less.

[0024] (sol.Al:0.4~1.50%) Al (aluminum) is an element that acts as a deoxidizing element. If the Al content is insufficient, there is a risk that sufficient deoxidizing effect cannot be secured. Furthermore, there is a risk that preferred oxides, particularly fine internal oxides of fine ferrite phase, are not sufficiently generated near the surface layer of the steel sheet. Al is contained in the internal oxide together with Si and Mn, functions as a pinning particle, and contributes to refinement of the ferrite phase. The Al content may be 0.4% or more, but in order to obtain a more sufficient amount of fine internal oxides of fine ferrite phase, the Al content is 0.5% or more, preferably 0.6% or more, and more preferably 0.7% or more. On the other hand, excessive Al content may cause a decrease in workability and deterioration of surface properties, and may also lead to promotion of external oxidation growth. Therefore, the Al content is 1.50% or less, preferably 1.20% or less, and more preferably 0.80% or less. The Al content means the content of so-called acid-soluble Al (sol.Al).

[0025] (P:0.0300% or less) P (phosphorus) is an impurity generally contained in steel. If the P content exceeds 0.0300%, the weldability may be reduced. Therefore, the P content is 0.0300% or less, preferably 0.0200% or less, more preferably 0.0100% or less, and further preferably 0.0050% or less. The lower limit of the P content is not particularly limited, but from the viewpoint of manufacturing costs, the P content may be more than 0% or 0.0001% or more.

[0026] (S:0.0300% or less) S (sulfur) is an impurity generally contained in steel. If the S content exceeds 0.0300%, the weldability is reduced, and furthermore, the amount of MnS precipitated increases, which may reduce workability such as bendability. Therefore, the S content is 0.0300% or less, preferably 0.0100% or less, more preferably 0.0050% or less, and further preferably 0.0020% or less. The lower limit of the S content is not particularly limited, but from the viewpoint of desulfurization costs, the S content may be more than 0% or 0.0001% or more.

[0027] (N:0.0100% or less) N (nitrogen) is an impurity generally contained in steel. If the N content exceeds 0.0100%, the weldability may be reduced. Therefore, the N content is 0.0100% or less, preferably 0.0080% or less, more preferably 0.0050% or less, and further preferably 0.0030% or less. There is no particular lower limit for the N content, but from the viewpoint of manufacturing costs, the N content may be more than 0% or 0.0010% or more.

[0028] (B: 0~0.010%) Since B (boron) is an element that improves hardenability and contributes to improving strength, and also segregates at grain boundaries to strengthen the grain boundaries and improve toughness, it may be contained as necessary. Therefore, the B content is 0% or more, preferably 0.001% or more, more preferably 0.002% or more, and even more preferably 0.003% or more. On the other hand, from the viewpoint of ensuring sufficient toughness and weldability, the B content is 0.010% or less, preferably 0.008% or less, and more preferably 0.006% or less.

[0029] (Ti: 0 to 0.150%) Ti (titanium) is an element that precipitates as TiC during cooling of steel and contributes to improving strength, so it may be contained as necessary. Therefore, the Ti content is 0% or more, preferably 0.001% or more, more preferably 0.003% or more, even more preferably 0.005% or more, and even more preferably 0.010% or more. On the other hand, if it is contained excessively, coarse TiN may be generated and toughness may be impaired, so the Ti content is 0.150% or less, preferably 0.100% or less, and more preferably 0.050% or less.

[0030] (Nb: 0~0.150%) Since Nb (niobium) is an element that contributes to improving strength through improving hardenability, it may be contained as necessary. Therefore, the Nb content is 0% or more, preferably 0.010% or more, more preferably 0.020% or more, and even more preferably 0.030% or more. On the other hand, from the viewpoint of ensuring sufficient toughness and weldability, the Nb content is 0.150% or less, preferably 0.100% or less, and more preferably 0.060% or less.

[0031] (V:0~0.150%) V (vanadium) is an element that contributes to improving strength through improving hardenability, so it may be contained as necessary. Therefore, the V content is 0% or more, preferably 0.010% or more, more preferably 0.020% or more, and even more preferably 0.030% or more. On the other hand, from the viewpoint of ensuring sufficient toughness and weldability, the V content is 0.150% or less, preferably 0.100% or less, and more preferably 0.060% or less.

[0032] (Cr:0~2.00%) Cr (chromium) is effective in increasing the hardenability of steel and increasing its strength, so it may be contained as necessary. Therefore, the Cr content is 0% or more, preferably 0.10% or more, more preferably 0.20% or more, even more preferably 0.50% or more, and even more preferably 0.80% or more. On the other hand, if it is contained in excess, a large amount of Cr carbide is formed, which may adversely impair the hardenability, so the Cr content is 2.00% or less, preferably 1.80% or less, and more preferably 1.50% or less.

[0033] (Ni: 0-2.00%) Ni (nickel) is effective in increasing the hardenability of steel and increasing the strength of steel, so it may be contained as necessary. Therefore, the Ni content is 0% or more, preferably 0.10% or more, more preferably 0.20% or more, even more preferably 0.50% or more, and even more preferably 0.80% or more. On the other hand, since excessive addition of Ni leads to an increase in cost, the Ni content is 2.00% or less, preferably 1.80% or less, and more preferably 1.50% or less.

[0034] (Cu: 0-2.00%) Cu (copper) is effective in increasing the hardenability of steel and increasing the strength of steel, so it may be contained as necessary. Therefore, the Cu content is 0% or more, preferably 0.10% or more, more preferably 0.20% or more, even more preferably 0.50% or more, and even more preferably 0.80% or more. On the other hand, from the viewpoint of suppressing a decrease in toughness, cracking of the slab after casting, and a decrease in weldability, the Cu content is 2.00% or less, preferably 1.80% or less, and more preferably 1.50% or less.

[0035] (Mo:0~1.00%) Mo (molybdenum) is effective in increasing the hardenability of steel and increasing the strength of steel, so it may be contained as necessary. Therefore, the Mo content is 0% or more, preferably 0.10% or more, more preferably 0.20% or more, and even more preferably 0.30% or more. On the other hand, from the viewpoint of suppressing the deterioration of toughness and weldability, the Mo content is 1.00% or less, preferably 0.90% or less, and more preferably 0.80% or less.

[0036] (W:0~1.00%) W (tungsten) is effective in increasing the hardenability of steel and increasing the strength of steel, so it may be contained as necessary. Therefore, the W content is 0% or more, preferably 0.10% or more, more preferably 0.20% or more, and even more preferably 0.30% or more. On the other hand, from the viewpoint of suppressing the deterioration of toughness and weldability, the W content is 1.00% or less, preferably 0.90% or less, and more preferably 0.80% or less.

[0037] (Ca: 0~0.100%) Ca (calcium) is an element that contributes to inclusion control, particularly to finely dispersing inclusions, and has the effect of increasing toughness, so it may be contained as necessary. Therefore, the Ca content is 0% or more, preferably 0.001% or more, more preferably 0.005% or more, even more preferably 0.010% or more, and even more preferably 0.020% or more. On the other hand, if it is contained excessively, deterioration of surface properties may become apparent, so the Ca content is 0.100% or less, preferably 0.080% or less, and more preferably 0.050% or less.

[0038] (Mg: 0~0.100%) Mg (magnesium) is an element that contributes to inclusion control, particularly to finely dispersing inclusions, and has the effect of increasing toughness, so it may be contained as necessary. Therefore, the Mg content is 0% or more, preferably 0.001% or more, more preferably 0.003% or more, and even more preferably 0.010% or more. On the other hand, if it is contained excessively, deterioration of surface properties may become apparent, so the Mg content is 0.100% or less, preferably 0.090% or less, and more preferably 0.080% or less.

[0039] (Zr: 0~0.100%) Zr (zirconium) is an element that contributes to inclusion control, particularly to finely dispersing inclusions, and has the effect of increasing toughness, so it may be contained as necessary. Therefore, the Zr content is 0% or more, preferably 0.001% or more, more preferably 0.005% or more, and even more preferably 0.010% or more. On the other hand, if it is contained excessively, deterioration of surface properties may become apparent, so the Zr content is 0.100% or less, preferably 0.050% or less, and more preferably 0.030% or less.

[0040] (Hf:0~0.100%) Hf (hafnium) is an element that contributes to inclusion control, particularly to finely dispersing inclusions, and has the effect of increasing toughness, so it may be contained as necessary. Therefore, the Hf content is 0% or more, preferably 0.001% or more, more preferably 0.005% or more, and even more preferably 0.010% or more. On the other hand, if it is contained excessively, deterioration of surface properties may become apparent, so the Hf content is 0.100% or less, preferably 0.050% or less, and more preferably 0.030% or less.

[0041] (REM:0~0.100%) REM (rare earth elements) are elements that contribute to inclusion control, particularly to finely dispersing inclusions, and have the effect of increasing toughness, and may be contained as necessary. Therefore, the REM content is 0% or more, preferably 0.001% or more, more preferably 0.005% or more, and even more preferably 0.010% or more. On the other hand, if contained excessively, deterioration of surface properties may become apparent, so the REM content is 0.100% or less, preferably 0.050% or less, and more preferably 0.030% or less. REM is an abbreviation for Rare Earth Metal, and refers to elements belonging to the lanthanoid series. REM is usually added as misch metal.

[0042] The balance of the steel sheet according to the present invention other than the above-mentioned composition is composed of Fe and impurities. Here, the impurities refer to components that are mixed in due to various factors in the manufacturing process, including raw materials such as ores and scraps, during industrial production of the steel sheet, and are allowed to be contained within a range that does not adversely affect the properties of the steel sheet according to the present invention.

[0043] In the present invention, the composition of the steel sheet may be analyzed by an elemental analysis method known to those skilled in the art, for example, by inductively coupled plasma mass spectrometry (ICP-MS). However, C and S may be measured by a combustion-infrared absorption method, and N may be measured by an inert gas fusion-thermal conductivity method. These analyses may be performed on samples of the steel sheet collected by a method conforming to JIS G0417:1999. In addition, when a plating layer is attached, the plating layer is dissolved in an acid solution to which an inhibitor that suppresses corrosion of the steel sheet is added, and the steel sheet from which the plating layer has been removed is subjected to ICP (inductively coupled plasma) emission spectroscopy to determine the composition of the steel sheet. The position at which the composition of the steel sheet is measured is preferably a region more than 1000 μm from the end of the pressure-welded portion of the spot weld. In the heat-affected zone (HAZ), the chemical composition of the steel plate may vary, making accurate measurement impossible. Therefore, it is preferable to measure the chemical composition in the so-called non-heat-affected zone (non-HAZ), which is a region more than 1000 μm from the end of the pressure weld of the spot weld and is not affected by the heat from welding.

[0044] The amount of sol. Al can be measured by the following procedure. Specifically, the steel sheet is electrolyzed, and the residue collected by filter paper is analyzed by inductively coupled plasma mass spectrometry. The detected amount of Al is the amount of precipitated Al. Meanwhile, the steel sheet is not electrolyzed, and T. Al (also called "total Al") is measured. The value obtained by subtracting the amount of precipitated Al from T. Al is defined as sol. Al.

[0045] [surface] In the present invention, the "surface layer" of a steel sheet means a region from the surface of the steel sheet (the interface between the steel sheet and the plating layer in the case of a plated steel sheet) to a predetermined depth in the sheet thickness direction, and the "predetermined depth" is typically 50 μm or less. The shape and number density of the fine ferrite phase and its internal oxides according to this embodiment are measured in a range of the "surface layer" from the steel sheet surface (the interface between the plating layer and the steel sheet) to a depth of 2 μm toward the steel sheet side. This range is sometimes referred to as the "surface vicinity". As will be described later, the spot welded portion includes a portion in which the steel sheet components and / or the plating layer components are melted and solidified, and it is difficult to distinguish the steel sheet surface (the interface between the plating layer and the steel sheet). Therefore, the "surface layer" and the "surface vicinity" are distinguished from the spot welded portion.

[0046] As illustrated in FIG. 3, in the plated steel sheet according to the preferred embodiment, a fine ferrite phase is present in the surface layer of the steel sheet, and fine internal oxides are present therein.

[0047] [Ferrite phase] In this embodiment, the term "ferrite phase" refers to a crystal phase that is a crystal grain constituting the matrix of steel and has a ferrite crystal structure. In reality, the ferrite phase is typically present three-dimensionally in a spherical or nearly spherical shape in the surface layer of the steel sheet, and therefore, when a cross section of the surface layer of the steel sheet is observed, the ferrite phase is typically observed in a circular or nearly circular shape.

[0048] (Circle equivalent diameter of ferrite phase) In this embodiment, the ferrite phase has a circle equivalent diameter of 1 μm (1000 nm) or less, and the ferrite phase in this range may be referred to as a fine ferrite phase. By controlling the circle equivalent diameter to this range, the fine ferrite phase can be dispersed near the surface layer of the steel sheet, and the fine inner oxide of the fine ferrite phase functions well as a trap site for Zn that may enter when a plated steel sheet having a plating layer formed on the steel sheet is welded. On the other hand, if the circle equivalent diameter exceeds 1 μm (1000 nm), the number of ferrite phases may decrease, and a preferable number density may not be obtained. The circle equivalent diameter of the ferrite phase is not particularly limited to a lower limit, but may be 2 nm or more, preferably 10 nm or more, so as to include the fine inner oxide described later.

[0049] (number density of ferrite phase) In a preferred embodiment, the number density of fine ferrite phases in the vicinity of the surface (the region from the surface to a depth of 2 μm) is 2 to 30 particles / μm. 2 By controlling the number density within this range, a large amount of fine ferrite phases can be dispersed in the surface layer of the steel sheet, and fine internal oxides can be contained within the fine ferrite phases. The fine internal oxides function well as trap sites for Zn that can penetrate when a plated steel sheet having a plating layer formed on the steel sheet is welded. Since the circle equivalent diameter of the ferrite phase is fine (circle equivalent diameter 1 μm or less) (compared to coarse ferrite phases), Zn that penetrates the ferrite phase quickly reaches the fine internal oxides, and the Zn is quickly trapped. Conversely, if the ferrite phase is coarse, it takes time for the Zn that penetrates the ferrite phase to reach the fine internal oxides, and the Zn may not be trapped. Therefore, when the number density of the fine ferrite phase is 2 particles / μm 2 If the number density of the fine ferrite phase is less than 3 / μm, the number of relatively coarse ferrite phases increases, and many of the fine internal oxides acting as Zn trapping sites are present in the coarse ferrite phases, which do not function adequately as Zn trapping sites, and there is a risk that good LME resistance cannot be obtained. 2 More preferably, 4 / μm 2More preferably, 5 / μm 2 The fine ferrite phase is preferably present in a large amount from the viewpoint of including fine internal oxides that function as Zn trap sites. However, under general manufacturing conditions, the upper limit of the number density of the fine ferrite phase is 30 pieces / μm 2 Therefore, the upper limit of the number density of the fine ferrite phase in the preferred embodiment is 30 particles / μm 2 Less than 25 particles / μm 2 Below, 20 pieces / μm 2 It may be the following.

[0050] The size (circle equivalent diameter) and number density of the ferrite phase are measured by a scanning electron microscope (SEM) and a transmission electron microscope (TEM). Specific measurements are as follows. A cross section of the surface layer of the steel sheet is observed by SEM to obtain an SEM image including the ferrite phase. A test piece for TEM observation is taken from the cross-sectional SEM image by FIB processing so as to include the interface between the plating layer and the steel sheet. In the TEM observation, a ferrite phase (circle equivalent diameter of 1 μm or less) corresponding to the shape shown in this embodiment is identified within a range of 2 μm deep from the steel sheet surface (interface between the plating layer and the steel sheet) to the steel sheet side, and its number density is measured. The observation position is 2.0 μm from the steel sheet surface in the depth direction (direction perpendicular to the steel sheet surface) and 1.0 μm from any position in the TEM image in the width direction (direction parallel to the steel sheet surface). In other words, the observation field area is 2.0 μm × 1.0 μm. Next, the TEM image of each region obtained as described above is extracted and binarized to separate each ferrite phase (and grain boundary (or phase interface)). The area of ​​each ferrite phase is calculated from each binarized image. The area of ​​each ferrite phase is calculated as the diameter of a circle having an area equal to the calculated area, i.e., the equivalent circle diameter (nm) of the ferrite phase is calculated as the equivalent circle diameter. Ferrite phases having an equivalent circle diameter of 1 μm or less (1000 nm or less) are defined as fine ferrite phases according to this embodiment. Furthermore, the number of fine ferrite phases in each binarized image is counted. The average number of fine ferrite phases in the total of the 10 regions thus calculated is taken as the number density of fine ferrite phases (pieces / μm 2Note that when only a part of the ferrite phase is observed in the observation area, that is, when the entire outline of the ferrite phase is not within the observation area, it is not counted.

[0051] [Fine internal oxide] In a preferred embodiment, the term "fine inner oxide" refers to an oxide present inside the fine "ferrite phase" described above. A plurality of fine inner oxides may be present in one ferrite phase, and the positions of the fine inner oxides may not be arranged according to a specific rule (for example, linearly) but may be arranged randomly.

[0052] (Grain size of fine internal oxides) In a preferred embodiment, the particle diameter of the fine internal oxide is 2 nm or more and 100 nm or less in equivalent circle diameter. By controlling the particle diameter within such a range, the fine internal oxide can be dispersed in the fine ferrite phase present in the vicinity of the surface layer of the steel sheet, and the fine internal oxide functions well as a trap site for Zn that may enter when a plated steel sheet having a plating layer formed on the steel sheet is welded. On the other hand, if the particle diameter exceeds 100 nm, the number of fine internal oxides may decrease, and a preferable number density may not be obtained. The finer the fine internal oxide, the higher the specific surface area and the higher the reactivity as a trap site, so the particle diameter of the fine internal oxide may be 50 nm or less, preferably 20 nm or less or less than 20 nm. On the other hand, the lower limit is 2 nm or more. The reason is that the amount of Zn that can be trapped per particle decreases, and Zn cannot be sufficiently trapped, and the fine internal oxide may not function sufficiently as a trap site for Zn. The shape of the fine inner oxide is not particularly limited, but the aspect ratio (maximum line length (major axis) crossing the fine inner oxide / maximum line length (minor axis) crossing the fine inner oxide perpendicular to the major axis) may be 1.5 or more, and the minor axis may be less than 20 nm. Without wishing to be bound by a particular theory, it is believed that when the aspect ratio of the fine inner oxide is high, the possibility of contacting Zn that has invaded the ferrite phase increases, and the Zn trapping efficiency increases.

[0053] (Number density of fine internal oxides) Preferably, the number density of the fine internal oxides is 3 particles / μm 2 That is all. By controlling the number density within this range, a large amount of fine inner oxides can be contained in the fine ferrite phase present in the surface layer of the steel sheet, and the fine inner oxides function well as trap sites for Zn that can enter when a plated steel sheet having a plated layer formed on the steel sheet is welded. On the other hand, when the number density is 3 particles / μm 2 If the number density of the fine internal oxides is less than 6 / μm, the number density of the fine internal oxides as Zn trap sites is insufficient, and the fine internal oxides do not function sufficiently as Zn trap sites, so that good LME resistance may not be obtained. 2 More preferably, 8 particles / μm 2 More preferably, 10 particles / μm 2 The fine inner oxides are preferably present in a large amount from the viewpoint of functioning as a trap site for Zn, but since the circle equivalent diameter of the ferrite phase including the fine inner oxides is 1 μm or less, the number density of the fine inner oxides may be set at an upper limit of 30 particles / μm. 2 Below, 25 pieces / μm 2 Below, 20 pieces / μm 2 It may be the following.

[0054] The particle size and number density of the fine internal oxides are measured by a scanning electron microscope (SEM) and a transmission electron microscope (TEM) in the same manner as for the ferrite phase. The specific measurement is as follows. The cross section of the surface layer of the steel sheet is observed by SEM to obtain an SEM image including the fine internal oxides. A test piece for TEM observation is taken from the cross-sectional SEM image by FIB processing so as to include the interface between the plating layer and the steel sheet. In the TEM observation, fine internal oxides (particle size 2 to 100 nm) corresponding to the shape shown in the preferred embodiment are identified within a range of 2 μm deep from the steel sheet surface (interface between the plating layer and the steel sheet) to the steel sheet side, and their number density is measured. The observation position is 2.0 μm from the steel sheet surface in the depth direction (direction perpendicular to the steel sheet surface) and 1.0 μm from any position in the TEM image in the width direction (direction parallel to the steel sheet surface). In other words, the observation field area is 2.0 μm × 1.0 μm. Next, the TEM image of each region obtained as described above is extracted and binarized to separate the fine inner oxide portion from the steel portion. The area of ​​the fine inner oxide portion is calculated from each binarized image, and the particle size (nm) of the fine inner oxide is calculated as the diameter of a circle having the same area as the calculated area, i.e., the circle equivalent diameter. Fine inner oxides with particle sizes in the range of 2 nm to 100 nm are defined as the fine inner oxides according to the preferred embodiment. Furthermore, the number of fine inner oxides in each binarized image is counted. The average number of fine inner oxides in the total of the 10 regions thus calculated is taken as the number density of the fine inner oxides (pieces / μm 2 Note that when only a part of a fine inner oxide is observed in the observation area, that is, when the entire outline of a fine inner oxide is not within the observation area, it is not counted.

[0055] [Composition of fine oxides] In a preferred embodiment, the fine inner oxide contains, in addition to oxygen, one or more of the elements contained in the steel sheet described above, and typically contains Si, O, and Fe, and may further contain Mn and Al. The fine inner oxide may contain elements (e.g., Cr, etc.) that may be contained in the steel sheet described above in addition to these elements. Although not wishing to be bound by a particular theory, it is believed that when the fine inner oxide contains Al, the effect as a Zn trap site is enhanced, and the content of Al contained in the fine inner oxide is preferably high, and may be 20 mass% or more. When the fine inner oxide is an oxide of Al and O, that is, so-called alumina, the Al content in the oxide is the highest, at 53 mass%, and this may be set as the upper limit of the Al content.

[0056] [Internal oxidation layer] In addition, in the plated steel sheet according to the present invention, an internal oxide layer is present in the surface layer of the steel sheet. In the manufacture of steel sheets, a heat treatment such as annealing is generally performed after rolling. In addition, Si, Mn, and Al, which are easily oxidized elements among elements typically contained in high-strength steel sheets, may combine with oxygen in the atmosphere during the heat treatment to form a layer containing oxides in the vicinity of the surface of the steel sheet. Examples of the form of such a layer include a form in which an oxide containing Si, Mn, or Al is formed as a film on the outside (surface) of the steel sheet (external oxide layer), and a form in which an oxide is formed inside (surface layer) of the steel sheet (internal oxide layer). In the present invention, the "internal oxide layer" refers to a region in the surface layer of the steel sheet that contains "granular oxides".

[0057] [Granular oxide] In the present invention, the term "granular oxide" refers to oxides dispersed in a granular shape in the crystal phase (the aggregate structure of crystal grains) of steel. However, the term "granular oxide" does not include fine internal oxides present in the fine ferrite phase. The term "granular" refers to oxides that are present apart from each other in the crystal phase of steel, and for example, refers to an aspect ratio (maximum line length (major axis) crossing the granular oxide / maximum line length (minor axis) crossing the oxide perpendicular to the major axis) of 1.0 to 5.0. The term "dispersed in a granular shape" refers to oxide particles that are not arranged according to a specific rule (for example, linearly) but are arranged randomly. In reality, the granular oxides are typically three-dimensionally present in a spherical or approximately spherical shape in the surface layer of the steel sheet, and therefore, when a cross section of the surface layer of the steel sheet is observed, the granular oxides are typically observed in a circular or approximately circular shape. In FIG. 4, a granular oxide 45 that appears approximately circular is shown as an example.

[0058] (particle size) In a preferred embodiment, the particle size of the granular oxide is 150 nm or more and 600 nm or less. By controlling the particle size in such a range, the granular oxide can be dispersed in the surface layer of the steel sheet, and the granular oxide functions well as a hydrogen trapping site that suppresses hydrogen penetration in a corrosive environment. On the other hand, if the particle size exceeds 600 nm, the number of granular oxides may decrease, and a preferable number density may not be obtained. The lower limit of the particle size of the granular oxide is 150 nm or more. The reason for setting the lower limit of the particle size of the granular oxide (150 nm) is to avoid a case where it becomes difficult to distinguish between fine internal oxides in a fine ferrite phase and granular oxides from the viewpoint of measurement accuracy. In addition, the finer the granular oxide, the higher the specific surface area becomes, and the higher the reactivity as a trapping site becomes, but the amount of hydrogen that can be trapped per particle decreases, and hydrogen cannot be sufficiently trapped, and there is a risk that the oxide does not function sufficiently as a hydrogen trapping site.

[0059] (number density of granular oxide) Preferably, the number density of the granular oxide is 4.0 pieces / 25 μm 2By controlling the number density within this range, a large amount of fine granular oxide can be dispersed on the surface layer of the steel sheet, and the granular oxide functions well as a hydrogen trap site that suppresses hydrogen penetration in a corrosive environment. 2 If the number density of the granular oxide is less than 6.0 / 25 μm, the number density of the granular oxide as a hydrogen trapping site is insufficient, and the granular oxide may not function adequately as a hydrogen trapping site. 2 More preferably, 8.0 pieces / 25μm 2 More preferably, 10.0 pieces / 25 μm 2 The more granular oxides there are, the better from the viewpoint of functioning as hydrogen trap sites. However, granular oxides can become the starting point of LME cracks, and the number of granular oxides is 30 / 25μm. 2 The number density of granular oxide is 30 pieces / 25μm because the LME resistance may decrease if the number exceeds 30 pieces / 25μm. 2 Below, 25 pieces / 25μm 2 Below, 20 pieces / 25μm 2 It may be the following.

[0060] The particle size and number density of the granular oxides are measured by a scanning electron microscope (SEM). The specific measurement is as follows. The cross section of the surface layer of the steel sheet is observed by SEM to obtain an SEM image containing the granular oxides. A total of 10 regions of 5.0 μm (depth direction) × 5.0 μm (width direction) are selected as observation regions from the SEM image. The observation position of each region is 5.0 μm from the steel sheet surface to 20.0 μm in the depth direction (direction perpendicular to the steel sheet surface), and 5.0 μm at any position in the above SEM image in the width direction (direction parallel to the steel sheet surface). Next, an SEM image of each of the regions selected as described above is extracted and binarized to separate the oxide portion from the steel portion. The area of ​​the granular oxide portion is calculated from each binarized image, and the particle size (nm) of the granular oxide is calculated as the diameter of a circle having the same area as the calculated area, i.e., the circle equivalent diameter. Particles with a particle size in the range of 150 nm to 600 nm are defined as granular oxides. Furthermore, the number of granular oxides in each binarized image is counted. The average number of granular oxides in the total of the 10 regions thus calculated is taken as the number density of granular oxides (particles / 25 μm 2 In addition, when only a part of a granular oxide is observed in the observation area, that is, when the entire outline of a granular oxide is not within the observation area, it is not counted.

[0061] [Composition of granular oxide] In the present invention, the granular oxide (hereinafter, simply referred to as oxide) contains, in addition to oxygen, one or more of the elements contained in the steel sheet described above, and typically has a composition containing Si, O, and Fe, and may further contain Mn and / or Al. The oxide may contain elements (e.g., Cr) that may be contained in the steel sheet described above.

[0062] <Plated steel sheets> The plated steel sheet according to the present invention has a plating layer containing Zn on the above-mentioned steel sheet according to the present invention. This plating layer may be formed on one side or both sides of the steel sheet. Examples of the plating layer containing Zn include a hot-dip galvanized layer, a galvannealed hot-dip galvanized layer, an electric galvanized layer, and an electric alloy galvanized layer. More specifically, examples of the plating type that can be used include Zn-0.2%Al (GI), Zn-(0.3 to 1.5)%Al, Zn-4.5%Al, Zn-0.09%Al-10%Fe (GA), Zn-1.5%Al-1.5%Mg, Zn-11%Al-3%Mg-0.2%Si, Zn-11%Ni, and Zn-15%Mg. In the present invention, the Zn-based plating layer may contain Zn, and also includes a plating layer in which the most abundant component is not Zn. Note that another layer may be included between the steel material and the Zn-based plating layer.

[0063] [Composition of Zn-based plating layer] The composition of the components contained in the Zn-based plating layer in a preferred embodiment will be described. Unless otherwise specified, "%" regarding the content of an element means "mass%". In the numerical range of the composition of the plating layer, a numerical range expressed with "~" means a range including the numerical values ​​written before and after "~" as the lower and upper limits, unless otherwise specified.

[0064] (Al: 0-60.0%) Since Al is an element that improves the corrosion resistance of the coating layer by being contained together with Zn or alloyed with Zn, it may be contained as necessary. Therefore, the Al content may be 0%. In order to form a coating layer containing Zn and Al, the Al content is preferably 0.01% or more, and may be, for example, 0.1% or more, 0.3% or more, 0.5% or more, 1.0% or more, or 3.0% or more. On the other hand, since the effect of improving the corrosion resistance is saturated when it exceeds 60.0%, the Al content is preferably 60.0% or less, and may be, for example, 55.0% or less, 50.0% or less, 40.0% or less, 30.0% or less, 20.0% or less, 10.0% or less, or 5.0% or less. Although the detailed mechanism is unknown, when the Al in the coating layer is in the range of 0.3 to 1.5%, the rate at which Zn penetrates into the steel grain boundary is significantly reduced due to the effect of Al, and it is possible to improve the LME resistance. Therefore, from the viewpoint of improving LME resistance, the Al content in the plating layer is preferably 0.3 to 1.5%. On the other hand, since the coating weight of electroplating is easily controlled by the amount of electricity, the Al content in the plating layer may be 0 to less than 0.1%. Typically, the plating layer may have a composition containing, by mass%, 0.3 to 1.5% Al with the balance being Zn and impurities, or the plating layer may have a composition containing, by mass%, 0 to less than 0.1% Al with the balance being Zn and impurities. A plating layer with a composition in this range can further improve LME resistance.

[0065] (Mg: 0-15.0%) Mg is an element that improves the corrosion resistance of the plating layer by being contained together with Zn and Al or alloyed with them, so it may be contained as necessary. Therefore, the Mg content may be 0%. In order to form a plating layer containing Zn, Al, and Mg, the Mg content is preferably 0.01% or more, and may be, for example, 0.1% or more, 0.5% or more, 1.0% or more, or 3.0% or more. On the other hand, if it exceeds 15.0%, Mg does not completely dissolve in the plating bath and floats as an oxide, and when zinc plating is performed with this plating bath, the oxide adheres to the plating surface layer, causing poor appearance, or there is a risk of non-plated parts occurring, so the Mg content is preferably 15.0% or less, and may be, for example, 10.0% or less, 5.0% or less.

[0066] (Fe: 0-15.0%) When a Zn-containing plating layer is formed on a steel sheet and then the plated steel sheet is heat-treated, Fe can be diffused from the steel sheet and contained in the plating layer. Therefore, in a state where no heat treatment is performed, Fe is not contained in the plating layer, and the Fe content may be 0%. The Fe content may be 1.0% or more, 2.0% or more, 3.0% or more, 4.0% or more, or 5.0% or more. On the other hand, the Fe content may be 15.0% or less, and may be, for example, 12.0% or less, 10.0% or less, 8.0% or less, or 6.0% or less.

[0067] (Si: 0-3.0%) Since Si is an element that further improves corrosion resistance when contained in a Zn-containing plating layer, particularly a Zn-Al-Mg plating layer, it may be contained as necessary. Therefore, the Si content may be 0%. From the viewpoint of improving corrosion resistance, the Si content may be, for example, 0.005% or more, 0.01% or more, 0.05% or more, 0.1% or more, or 0.5% or more. In addition, the Si content may be 3.0% or less, 2.5% or less, 2.0% or less, 1.5% or less, or 1.2% or less.

[0068] The basic composition of the plating layer is as described above. Furthermore, the plating layer may optionally contain one or more of Sb: 0-0.50%, Pb: 0-0.50%, Cu: 0-1.00%, Sn: 0-1.00%, Ti: 0-1.00%, Sr: 0-0.50%, Cr: 0-1.00%, Ni: 0-1.00%, and Mn: 0-1.00%. Although not particularly limited, from the viewpoint of fully exerting the action and function of the above basic components constituting the plating layer, the total content of these optional added elements is preferably 5.00% or less, more preferably 2.00% or less.

[0069] The remainder of the plating layer other than the above components is composed of Zn and impurities. The impurities in the plating layer refer to components that are mixed in due to various factors in the manufacturing process, including raw materials, when the plating layer is manufactured, and are not components that are intentionally added to the plating layer. The plating layer may contain trace amounts of elements other than the basic components and optional added components described above as impurities within a range that does not impair the effects of the present invention.

[0070] The composition of the plating layer can be determined by dissolving the plating layer in an acid solution containing an inhibitor that suppresses corrosion of the steel sheet, and measuring the resulting solution by ICP (inductively coupled plasma) optical emission spectroscopy. In the steel weld according to this embodiment, the position for measuring the composition of the plating layer is preferably a region more than 1000 μm from the end of the pressure weld of the spot weld. In the heat-affected zone (HAZ), the composition of the plating layer may vary, and accurate measurement may not be possible. Therefore, it is preferable to measure the composition in a so-called non-heat-affected zone (non-HAZ) that is not affected by heat from welding and is more than 1000 μm from the end of the pressure weld of the spot weld.

[0071] The thickness of the plating layer may be, for example, 3 to 50 μm. The coating weight of the plating layer is not particularly limited, but is, for example, 10 to 170 g / m per side. 2In the present invention, the coating weight of the plating layer is determined by dissolving the plating layer in an acid solution to which an inhibitor that suppresses corrosion of the base steel has been added, and measuring the change in weight before and after dissolution of the plating.

[0072] [Spot welds] The steel welded member according to the present invention includes at least one spot weld between the Zn-based plated steel materials described above. Thus, a plurality (two or more) of Zn-based plated steel materials are joined by spot welding. FIG. 1 is a cross-sectional view for explaining a spot weld of an exemplary steel welded member according to the present invention. In FIG. 1, two Zn-based plated steel materials 11 are joined via a spot weld 21. Usually, when two Zn-based plated steel materials 11 are spot-welded, a portion called a nugget portion 23 in which steel components and / or plating layer components are melted and solidified is formed in the portion pressed by the electrode, as shown in FIG. 1, and a pressure-welded portion 25 in which the components are joined without melting is formed outside the nugget portion 23. Thus, the spot welded portion 21 includes the nugget portion 23 and the pressure-welded portion 25, and is typically composed of only the nugget portion 23 and the pressure-welded portion 25. The nugget portion 23 and the pressure-welded portion 25 have different component compositions, and therefore can be easily distinguished, for example, by a backscattered electron image (BSE image) of a scanning electron microscope (SEM). In the present invention, the shape and composition of the nugget portion 23 are not particularly limited.

[0073] (Pressure welded part) In the steel welded member according to the present invention, in a region 10 to 300 μm from the end of the pressure welded portion of the spot weld, the difference between the Zn penetration depth of Zn from the Zn-based plating layer into the steel material and the depth of the internal oxide layer formed in the steel material is within a range of 0.1 to 10 μm (the Zn penetration depth is deep). Preferably, the difference between the Zn penetration depth and the depth of the internal oxide layer is within a range of 1.5 to 10 μm (the Zn penetration depth is deep). Here, in the present invention, the "end of the pressure welded portion" refers to the end of the spot welded portion of a plurality of Zn-based plated steel materials, and is the boundary between the portion where the plurality of Zn-based plated steel materials are joined by welding (pressure welded portion) and the portion where they are not joined. More specifically, the "end of the pressure welded portion" is present within the dashed line in FIG. 1 and is represented by the number 27 in FIG. 2. Therefore, the "region 10 to 300 μm from the end of the pressure weld" refers to the region of the Zn-based plated steel material extending from the boundary (number 27 in FIG. 2) between the joint 25 and the non-joint portion 28 (also called the separation portion 28) of the two Zn-based plated steel materials in the opposite direction to the nugget portion 23 (to the right in FIG. 2) up to 10 to 300 μm. In FIG. 2, the plating layer in that region is indicated by number 29 (shaded). Hereinafter, the region 10 to 300 μm from the end of the pressure welded portion of the spot weld is also simply referred to as the "region near the end."

[0074] (Zn penetration depth) In the steel welded member according to the present invention, Zn penetrates from the Zn-based coating layer into the steel material in the region near the end, and the penetration depth is also simply referred to as the "Zn penetration depth". The Zn penetration depth can be easily identified by performing elemental analysis of the cross-sectional structure of the steel material using SEM-EDS to obtain the Zn composition ratio. The starting point of the depth is the steel sheet surface (the interface between the coating layer and the steel sheet), and the Zn penetration depth is larger (deeper) as it advances further into the steel material. Since the Zn penetration depth may vary depending on the measurement location, the SEM magnification is set to 2000 times or more, and five arbitrary fields of view (each field of view area is 30 μm × 30 μm) are selected, and the position where the interface between the coating layer and the steel material (base steel) is near the center of the field of view is observed, and the maximum Zn penetration depth among the five fields of view is taken as the "Zn penetration depth".

[0075] Although not wishing to be bound by a particular theory, in the present invention, the following is considered to be the mechanism by which Zn from the Zn-based coating layer penetrates into the steel material. The Zn contained in the coating layer melts in the region near the end due to welding. The molten Zn diffuses from the interface of the steel sheet on which the coating layer is provided (the interface between the coating layer and the steel sheet) in the depth direction of the steel sheet. At this time, the molten Zn diffuses along the grain boundaries of the crystal grains constituting the steel sheet structure, and also diffuses from the grain boundaries into the grains of the crystal grains. If fine internal oxides exist within the crystal grains, the Zn is trapped by the fine internal oxides. In a preferred embodiment, the ferrite phase near the surface layer of the steel sheet is fine (compared to when the ferrite phase is coarse), so there are many paths of grain boundaries (or phase interfaces) and the distance from the grain boundaries (or phase interfaces) to the fine internal oxides within the grains (or phases) is short, so that the molten Zn is quickly trapped by the fine internal oxides within the ferrite phase. This trapping action is repeated from the interface toward the inside of the steel sheet, causing Zn from the Zn-based coating layer to penetrate into the inside of the steel material. Even if Zn diffuses into the surface layer of the steel sheet, the metal structure of the surface layer of the steel sheet is typically composed of a metal structure that is softer than the inside of the steel sheet (for example, at the 1 / 8 or 1 / 4 position of the sheet thickness), so liquid metal embrittlement (LME) cracking does not pose a particular problem even if Zn is present (diffused) in the surface layer of the steel sheet.

[0076] (depth of internal oxide layer) In the steel sheet according to the present invention, the internal oxide layer is a layer formed inside the steel sheet and includes granular oxide 45. Therefore, the "internal oxide layer" is a region that is continuous from the surface of the steel sheet to the furthest position where granular oxide exists. Therefore, the "depth of the internal oxide layer" refers to the distance from the surface of the steel sheet 41 (the interface between the steel sheet and the plating layer in the case of a plated steel sheet) to the furthest position where granular oxide 45 exists, as shown as "Rn" in FIG. 4, when moving from the surface of the steel sheet 41 (the interface between the steel sheet and the plating layer in the case of a plated steel sheet) in the thickness direction of the steel sheet 41 (the direction perpendicular to the surface of the steel sheet). However, since the surface of an actual steel sheet is uneven, the position of the furthest granular oxide 45 from the steel sheet surface varies depending on which location (point) on the steel sheet surface is selected, 10 observation regions (the field of view of each observation region is 30 μm×30 μm) are selected at appropriate measurement intervals in the cross-sectional lateral direction of the steel sheet 41 (the direction parallel to the surface of the steel sheet 41) within the range of the end vicinity region. The 10 observation regions may overlap, but are adjusted so that the total length L0 of the width of the steel sheet to be observed is substantially 100 μm. In the measurement results, the distance from the surface of the steel sheet to the farthest position where the granular oxide exists is defined as the "depth of the internal oxide layer" (Rn). The average value of the depth of the internal oxide layer in each of the 10 observation regions is defined as the "average depth of the internal oxide layer" (sometimes referred to as "R"). In FIG. 4, the distance from the surface of the steel sheet to the granular oxide 45 existing at the deepest position is shown as an example of the "depth of the internal oxide layer" (Rn). In the steel sheet according to the present invention, the lower limit of the average depth R of the internal oxide layer is not particularly limited, but if it is too shallow, the granular oxide 45 may not be sufficiently dispersed, so it is 1.0 μm or more, preferably 2.0 μm or more, more preferably 3.0 μm or more, and even more preferably 4.0 μm or more. The upper limit of the average depth R is not particularly limited, but is substantially 30 μm or less.

[0077] The depth Rn of the internal oxide layer is determined by observing a cross section of the surface layer of the steel sheet 41, as shown in FIG. 4. The specific measurement method is as follows. The cross section of the surface layer of the steel sheet 41 is observed by SEM. As for the observation position, one point is randomly selected within the range of the region near the end, and from there, a total of 10 observation regions (the field of view of each observation region is 30 μm × 30 μm) are selected at appropriate measurement intervals. The length L of the surface (i.e., the width of the SEM image) is measured from the SEM image observed for each observation region. Although the 10 observation regions may overlap, the total length L0 of the width of the steel sheet to be observed is substantially 100 μm, and the measurement depth is the region from the surface of the steel sheet to 30 μm. Next, the position of the granular oxide 45 is identified from the SEM image of each of the 10 observation regions, and one of the granular oxides 45 located at the farthest position from the surface of the steel sheet is selected from the identified granular oxides 45. The distance from the surface of the steel sheet 41 to the farthest position where any of the granular oxides 45 exists is measured as the "depth of the internal oxide layer in each observation region." From the measurement results of the 10 observation regions, the distance from the surface of the steel sheet 41 to the farthest position where any of the granular oxides 45 exists is determined as the "depth of the internal oxide layer" (Rn). The average value of the "depth of the internal oxide layer in each observation region" measured at the 10 positions is determined as the "average depth of the internal oxide layer" (sometimes referred to as "R").

[0078] (Zn penetration depth - internal oxide layer depth ≧ 0.1 μm) FIG. 5 is a schematic diagram for explaining the relationship between the Zn penetration depth and the internal oxide layer depth. In general, the Zn penetration depth of the surface layer of the steel material is larger (deeper) than the internal oxide layer depth, which means that the molten metal such as Zn diffuses into the crystal grains constituting the structure of the surface layer of the steel material and reaches a position deeper than the granular internal oxide. If the difference in depth is 0.1 μm or more, Zn, etc., diffuses sufficiently into the metal crystal grains of the steel sheet surface layer, and the penetration of Zn, etc. into the crystal grain boundaries is relatively suppressed, and the LME resistance is improved. The deeper the penetration depth of Zn, the more the diffusion of Zn, etc. into the crystal grains progresses, the more the penetration of Zn, etc. into the crystal grains is suppressed, and the LME resistance is improved, which is preferable. Therefore, Zn penetration depth-internal oxide layer depth≧1.5 μm may be satisfied. More preferably, the difference may be 2.0 μm or more, and even more preferably 3.0 μm or more. On the other hand, if the difference is too large, the effect of improving the LME resistance is saturated, so the upper limit of the difference may be set to 10.0 μm. That is, Zn penetration depth-internal oxide layer depth≦10.0 μm.

[0079] <Method of manufacturing steel welded components> A preferred method for manufacturing the welded steel component according to the present invention will be described below. The following description is intended to be an example of a characteristic method for manufacturing the welded steel component according to the present invention, but is not intended to limit the welded steel component to one manufactured by the manufacturing method described below.

[0080] The steel welded member according to the present invention can be obtained by carrying out a steel material preparation step of preparing a steel material, a plating step of forming a Zn-based plating layer on the surface of each steel material to prepare a Zn-based plated steel material, and a welding step of joining two plated steel materials by spot welding. In order to obtain the steel welded member according to the present invention, more specifically, a steel welded member in which the difference between the Zn penetration depth of Zn from the Zn-based plating layer into the steel material in the end vicinity region and the depth of the internal oxide layer formed in the steel material is within the range of 0.1 to 10.0 μm, it is effective to form a fine ferrite phase in the surface layer of the steel material and fine internal oxides therein in the steel material preparation step. When the Zn-based plating layer is formed and then spot-welded in a state in which the fine ferrite phase and the fine internal oxide are formed in the steel material, the molten Zn and other components of the plating layer flow out near the end of the pressure welded part, i.e., in the end vicinity region, and the molten Zn diffuses from the interface of the steel sheet with the plating layer (the interface between the plating layer and the steel sheet) in the depth direction of the steel sheet. At this time, the molten Zn diffuses through the grain boundaries of the crystal grains that constitute the steel sheet structure, and also diffuses from the grain boundaries into the grain interiors of the crystal grains. Since the ferrite phase near the steel sheet surface is fine (compared to when the ferrite phase is coarse), there are many paths of the grain boundaries (or phase interfaces), and the distance from the grain boundaries (or phase interfaces) to the internal oxides in the grains (or phases) is short, so that the molten Zn is quickly trapped by the internal oxides of the ferrite phase. Therefore, Zn, etc. diffuse sufficiently into the metal crystal grains in the steel sheet surface, and the intrusion of Zn, etc. into the grain boundaries is relatively suppressed, improving the LME resistance. In order to form a fine ferrite phase in the surface layer of the steel material and fine internal oxides therein, it is effective to perform an annealing process under predetermined conditions after rolling and then a predetermined annealing pretreatment process (grinding process). In the following, the steel material preparation process, plating process, and welding process will be described using a case where a steel sheet is used as the steel material. The steel material may be in any shape, and when a steel material other than a steel plate is used, the method for manufacturing the welded steel component may be modified as appropriate according to techniques known in the art.

[0081] <Steel sheet manufacturing method> A preferred method for producing the steel plate according to the present invention will be described below. The following description is intended to exemplify a characteristic method for producing the steel plate according to the present invention, and is not intended to limit the steel plate to one produced by the production method described below.

[0082] The steel sheet according to the present invention can be obtained by, for example, carrying out a casting process in which molten steel with an adjusted composition is cast to form a steel slab, a hot rolling process in which the steel slab is hot rolled to obtain a hot rolled steel sheet, a coiling process in which the hot rolled steel sheet is coiled, a cold rolling process in which the coiled hot rolled steel sheet is cold rolled to obtain a cold rolled steel sheet, a pickling process in which the cold rolled steel sheet is pickled, a pretreatment process in which the pickled cold rolled steel sheet is brush ground, and an annealing process in which the pretreated cold rolled steel sheet is annealed. Alternatively, the cold rolling process may be carried out directly after pickling without coiling after the hot rolling process.

[0083] [Casting process] The conditions for the casting process are not particularly limited. For example, after melting in a blast furnace or an electric furnace, various secondary smelting processes may be carried out, and then casting may be carried out by a method such as ordinary continuous casting or casting by an ingot method.

[0084] [Hot rolling process] The cast steel slab as described above can be hot-rolled to obtain a hot-rolled steel sheet. The hot rolling step is performed by hot-rolling the cast steel slab directly or after cooling it once and then reheating it. When reheating is performed, the heating temperature of the steel slab may be, for example, 1100°C to 1250°C. In the hot rolling step, rough rolling and finish rolling are usually performed. The temperature and reduction of each rolling step may be appropriately changed depending on the desired metal structure and plate thickness. For example, the finishing temperature of the finish rolling may be 900 to 1050°C, and the reduction of the finish rolling may be 10 to 50%.

[0085] [Winding process] The hot-rolled steel sheet can be coiled at a predetermined temperature. The coiling temperature may be appropriately changed depending on the desired metal structure, etc., and may be, for example, 500 to 800°C. The hot-rolled steel sheet may be recoiled before or after coiling and subjected to a predetermined heat treatment. Alternatively, the coiling step may be omitted, and the hot-rolled steel sheet may be pickled after the hot-rolling step and then subjected to the cold-rolling step described below.

[0086] [Cold rolling process] After the hot-rolled steel sheet is subjected to pickling or the like, the hot-rolled steel sheet is cold-rolled to obtain a cold-rolled steel sheet. The rolling reduction in the cold rolling may be appropriately changed depending on the desired metal structure and sheet thickness, and may be, for example, 20 to 80%. After the cold rolling process, the steel sheet may be cooled to room temperature, for example, by air cooling.

[0087] [Pretreatment process] In order to obtain a fine ferrite phase and fine internal oxides therein in the surface layer of the finally obtained steel sheet, it is effective to carry out a predetermined pretreatment process before annealing the cold-rolled steel sheet. The pretreatment process makes it possible to more effectively introduce strain into the steel sheet, and the strain promotes dislocations in the metal structure of the steel sheet, which makes it easier for oxygen to penetrate into the steel along the dislocations during annealing, making it easier to generate oxides inside the steel sheet. As a result, this is advantageous for increasing the number density of internal oxides in the ferrite phase. In addition, the internal oxides function as pinning particles and contribute to the refinement of the ferrite phase. Therefore, when such a pretreatment process is carried out, it is easy to generate the desired fine ferrite phase and fine internal oxides therein in the annealing process described later. The pretreatment process includes grinding the surface of the cold-rolled steel sheet with a heavy-duty grinding brush (brush grinding process). As the heavy-duty grinding brush, D-100 manufactured by Hotani Co., Ltd. may be used. When grinding, it is recommended to apply a 1.0 to 5.0% NaOH aqueous solution to the surface of the steel sheet. The brush reduction amount is preferably 0.5 to 10.0 mm, and the rotation speed is preferably 100 to 1000 rpm. By performing the brush grinding treatment under such coating liquid conditions, brush reduction amount, and rotation speed, a fine ferrite phase and its internal oxides can be efficiently formed in the vicinity of the surface layer of the steel sheet in the annealing step described later.

[0088] [Annealing process] The cold-rolled steel sheet that has been subjected to the above pretreatment process is annealed. Annealing is preferably performed under tension of, for example, 0.1 to 20 MPa. Applying tension during annealing makes it possible to introduce strain into the steel sheet more effectively, and the strain promotes dislocations in the metal structure of the steel sheet, which makes it easier for oxygen to penetrate into the steel along the dislocations, making it easier for oxides to be generated inside the steel sheet. As a result, this is advantageous for increasing the number density of fine internal oxides in the fine ferrite phase.

[0089] From the viewpoint of generating a fine ferrite phase and fine internal oxides therein, the holding temperature in the annealing step is preferably 700°C to 900°C. If the holding temperature in the annealing step is less than 700°C, the internal oxides may not be generated in a sufficient amount. In addition, the pinning effect of the ferrite phase grain boundary by the internal oxides may be insufficient, and the ferrite phase may become coarse. Therefore, the LME resistance may be insufficient, and sufficient strength may not be obtained. On the other hand, if the holding temperature in the annealing step is more than 900°C, the internal oxides may become coarse, and the desired internal oxides may not be generated. In addition, if the temperature is more than 900°C, even if the internal oxides are formed, the ferrite phase may grow rapidly and the desired fine ferrite phase may not be obtained. Therefore, the LME resistance may be insufficient. The heating rate to the above holding temperature is not particularly limited, but may be 1 to 10°C / sec. The temperature may be increased in two stages, that is, at a first rate of increase in temperature of 1 to 10° C. / sec and a second rate of increase in temperature of 1 to 10° C. / sec that is different from the first rate of increase in temperature.

[0090] The holding time at the holding temperature in the annealing step may be 0 to 300 seconds, and preferably 50 to 130 seconds. Holding time of 0 seconds means that the temperature rise process is heat treated at a predetermined dew point, and immediately after reaching the predetermined temperature, the material is cooled without isothermal holding. Even if the holding time is 0 seconds, fine internal oxides are generated during the temperature rise process, and LME resistance can be obtained. On the other hand, if the holding time is longer than 300 seconds, the internal oxides may become coarse, and the LME resistance may become insufficient.

[0091] During the temperature rise and holding (isothermal) of the annealing process, humidification is performed from the viewpoint of generating fine ferrite phases and fine internal oxides therein. Humidification is started at least from 300°C during the temperature rise. At 300°C or higher, dislocations in the ferrite phase in the steel sheet act as oxygen diffusion paths, and the generation of internal oxides in the ferrite phase by oxygen contained in the humidified atmosphere is promoted. In general, humidification during the temperature rise from about 300°C to the holding temperature promotes the formation of an external oxide film and reduces platability, so those skilled in the art avoid humidification from such a temperature rise process. In addition, when the temperature at which humidification is started exceeds 300°C, particularly at a temperature close to the holding temperature, for example, a temperature of about 700°C, the dislocations in the ferrite phase are restored and disappeared, so that internal oxides in the ferrite phase are not sufficiently generated.

[0092] The atmosphere for humidification has a dew point of more than 10° C. and not more than 20° C., preferably 11 to 20° C., and a hydrogen concentration of 8 to 20 vol% H2, preferably 10 vol% H2. The dew point before humidification is −40 to −60° C., and water vapor is added from there to control the dew point to a predetermined value. If the dew point is too low, fine internal oxides may not be formed sufficiently. In addition, the pinning effect of the internal oxides on the ferrite grain boundaries may be insufficient, causing the ferrite phase to coarsen. As a result, LME resistance may be insufficient. On the other hand, if the dew point is too high, an outer oxide layer may be formed on the surface of the steel sheet, making it difficult to obtain a plating layer. Even if the dew point is within the above range, if the hydrogen concentration is too low, the oxygen potential becomes excessive, and an outer oxide layer is formed, which may result in the plating layer not being obtained, or the inner oxide layer may not be formed sufficiently, resulting in insufficient LME resistance. On the other hand, if the hydrogen concentration is too high, the oxygen potential becomes insufficient, and the inner oxide layer is not formed sufficiently, and an outer oxide layer is formed, which may result in a failure to obtain a plating layer. Also, if a sufficient amount of inner oxide is not generated, the pinning effect of the inner oxide on the ferrite phase grain boundary becomes insufficient, and the ferrite phase may become coarse. As a result, the LME resistance may be insufficient.

[0093] Furthermore, when performing the annealing process, it is effective to remove the internal oxide layer of the steel sheet, particularly before the brush grinding process. An internal oxide layer may be formed on the surface layer of the steel sheet during the above-mentioned rolling process, particularly the hot rolling process. Such an internal oxide layer formed in the rolling process may hinder the formation of fine internal oxides in the annealing process, and may also cause the pinning effect of the ferrite phase grain boundary by the internal oxide to be insufficient, resulting in coarsening of the ferrite phase. Therefore, it is preferable to remove the internal oxide layer before annealing by pickling or the like. More specifically, the depth of the internal oxide layer of the cold-rolled steel sheet when performing the annealing process is set to 0.5 μm or less, preferably 0.3 μm or less, more preferably 0.2 μm or less, and even more preferably 0.1 μm or less.

[0094] By carrying out each of the above-mentioned steps, a steel sheet having a fine ferrite phase formed on the surface layer of the steel sheet and fine internal oxides formed therein can be obtained.

[0095] <Method of manufacturing plated steel sheets> A preferred method for producing the plated steel sheet according to the present invention will be described below. The following description is intended to exemplify a characteristic method for producing the plated steel sheet according to the present invention, but is not intended to limit the plated steel sheet to one produced by the production method described below.

[0096] The plated steel sheet according to the present invention can be obtained by carrying out a plating treatment step of forming a plating layer containing Zn on the steel sheet produced as described above.

[0097] [Plating process] The plating process may be carried out according to a method known to those skilled in the art. The plating process may be carried out, for example, by hot-dip plating or by electroplating. Preferably, the plating process is carried out by hot-dip plating. The conditions of the plating process may be appropriately set in consideration of the component composition, thickness, and coating weight of the desired plating layer. After the plating process, an alloying process may be carried out. Typically, the conditions of the plating process may be set so as to form a plating layer containing Al: 0-60.0%, Mg: 0-15.0%, Fe: 0-15%, Ni: 0-20%, and Si: 0-3%, with the balance being Zn and impurities. More specifically, the conditions of the plating process may be appropriately set to form, for example, Zn-0.2%Al (GI), Zn-0.8%Al, Zn-4.5%Al, Zn-0.09%Al-10%Fe (GA), Zn-1.5%Al-1.5%Mg, or Zn-11%Al-3%Mg-0.2%Si, Zn-11%Ni, or Zn-15%Mg. From the viewpoint of improving LME resistance, the Al content in the plating layer is preferably 0.3 to 1.5%.

[0098] <Welding process> In the welding process, two or more Zn-based plated steel sheets are prepared, and spot welding is performed at at least one location. Therefore, a spot weld is formed between the two steel sheets by the welding process, and as a result, a steel welded member can be obtained in which a plurality of Zn-based plated steel materials having a Zn-based plated layer on the surface of the steel sheet are joined via at least one spot weld. If at least one of the Zn-based plated steel sheets is obtained by the above-mentioned exemplary manufacturing process, the effect of improving LME resistance can be obtained in the plated steel sheet. Naturally, if the counterpart material of the welding is a plated steel sheet of the same quality as the at least one Zn-based plated steel material, the effect of improving LME resistance can also be obtained in the counterpart material. The conditions for spot welding may be conditions known to those skilled in the art. For example, a dome radius type welding electrode with a tip diameter of 6 to 8 mm can be used, with a pressure of 1.5 to 6.0 kN, a current flow time of 0.1 to 1.0 s (5 to 50 cycles, power supply frequency of 50 Hz), and a current flow of 4 to 15 kA.

[0099] As described above, when manufacturing steel welded components, a steel material having a fine ferrite phase with fine internal oxides therein is produced by going through specified steel preparation processes (particularly the brushing process and annealing process), and this steel material is then Zn-based plated to produce a Zn-based plated steel material, which can produce a steel welded component in which the difference between the Zn penetration depth of Zn from the Zn-based plated layer into the steel material, minus the depth of the internal oxide layer formed on the steel material, in the region near the end of the pressure welded part of the spot weld is within the range of 0.1 to 10.0 μm. EXAMPLES

[0100] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. Unless otherwise specified, samples were prepared according to the following procedure. In some comparative examples, specific conditions used will be described separately.

[0101] Examples and Comparative Examples of Plated Steel Sheets (Preparation of steel samples) The molten steel with the adjusted composition was cast to form a steel billet, which was then hot-rolled, pickled, and cold-rolled to obtain a cold-rolled steel sheet. The cold-rolled steel sheet was then air-cooled to room temperature, and pickled to remove the internal oxide layer formed by rolling to the depth (μm) of the internal oxide layer before annealing shown in Table 1. Samples were then taken from each cold-rolled steel sheet in accordance with JIS G0417:1999, and the composition of the steel sheet was analyzed by ICP-MS or the like. The measured composition of the steel sheet is shown in Tables 1 and 2. The thickness of all the steel sheets used was 1.6 mm.

[0102] Next, a 2.0% aqueous solution of NaOH was applied to some of the cold-rolled steel sheets, and the sheets were pretreated by brush grinding with a heavy-duty grinding brush (D-100 manufactured by Hotani Co., Ltd.) at a brush reduction of 2.0 mm and a rotation speed of 600 rpm. Thereafter, the sheets were annealed at the hydrogen concentration, dew point, holding temperature and holding time shown in Tables 1 and 2 to prepare each steel sheet sample. The presence or absence of pretreatment and the conditions of the annealing treatment (humidification zone, hydrogen concentration (%), dew point (°C), holding temperature (°C), and holding time (seconds)) are shown in Tables 1 and 2. "Temperature increase" in the column of the humidification zone means that the sheet is humidified in an atmosphere with the aforementioned hydrogen concentration and dew point during the period from 300°C or higher to the holding temperature, and "isothermal" in the column of the humidification zone means that the sheet is humidified in an atmosphere with the aforementioned hydrogen concentration and dew point during the holding time. The temperature increase rate during annealing was 1 to 10°C / second. In the above annealing treatment, the cold-rolled steel sheets were subjected to a tension of 0.1 to 20 MPa or more in the rolling direction. For each steel sheet sample, a JIS No. 5 tensile test piece was taken with the longitudinal direction perpendicular to the rolling direction, and a tensile test was performed in accordance with JIS Z 2241 (2011). As a result, the tensile strength of Nos. 22 and 26 was less than 780 MPa, and the rest were 780 MPa or more.

[0103] (Preparation of Zn-plated steel samples) After each steel sample was cut to a size of 100 mm × 200 mm, a plating process was performed to form the plating types shown in Tables 1 and 2, to prepare plated steel samples. In Tables 1 and 2, plating type a means "galvannealed steel sheet (GA)", plating type b means "hot-dip Zn-0.2% Al plated steel sheet (GI)", plating type c means "hot-dip Zn-(0.3-1.5)% Al plated steel sheet (Al content shown in Tables 1 and 2)", and plating type d means "electrolytic Zn plating (Al composition less than 0.01%)". In the hot-dip galvanizing process, the cut samples were immersed in a hot-dip galvanizing bath at 440 °C for 3 seconds. After immersion, the samples were pulled out at 100 mm / s, and the coating weight was reduced to 50 g / m by N2 wiping gas. 2The temperature was controlled to 500°C. For the coating type a, an alloying treatment was then performed at 500°C. Regarding the LME resistance described below, when the Al content was 0.3 to 1.5 mass% for the coating type c and when the electrolytic Zn plating was used for the coating type d, the LME resistance was improved. The results are shown in Tables 1 and 2.

[0104] The obtained plated steel samples were evaluated for each evaluation item using the following evaluation methods. For each plated steel sample, a JIS No. 5 tensile test piece was taken with the longitudinal direction perpendicular to the rolling direction, and a tensile test was performed in accordance with JIS Z 2241 (2011). As a result, the tensile strength of No. 22 and 26 was less than 780 MPa, and the rest were 780 MPa or more. The results are shown in Tables 1 and 2.

[0105] (Preparation of steel welded component samples) Each Zn-based plated steel sample was cut to a size of 50 mm x 100 mm to prepare two pieces, and the two Zn-based plated steel sheet samples were spot-welded to obtain steel welded component samples. The spot welding conditions were a dome radius type welding electrode with a tip diameter of 8 mm, an impact angle of 5°, a pressure of 4.0 kN, a current flow time of 0.5 seconds, and a current flow current of 8 kA, and the steel welded component evaluation samples were obtained under the same welding conditions as the other samples, except that the current flow for sample No. 43 was 9 kA.

[0106] (Analysis of the structure in the region 10 to 300 μm from the edge of the pressure weld) For each evaluation sample, the structure of the region 10 to 300 μm from the end of the pressure weld (region near the end) was analyzed using SEM observation and EDS analysis of the cross section of the weld. Specifically, the cross section was first polished in a direction perpendicular to the direction of the stroke angle by spot welding to prepare a cross-sectional sample of the weld, and then a BSE image including the end of the pressure weld was obtained by SEM. The end of the pressure weld was identified from the BSE image, and then a region 10 to 300 μm from the end of the pressure weld of the spot weld (region near the end) was identified. In the steel (base steel) part in the identified region near the end, the BSE image was binarized to distinguish between "granular oxide" and "crystal phase of steel (assembly of crystal grains)," thereby identifying the outline of the granular oxide, and the major axis, number, position, etc. of each observed oxide were measured. In addition, the "depth of the internal oxide layer" including the granular oxide was calculated based on the binarized image. Cracks and gaps in the BSE image were identified from oxides using an elemental analysis SEM-EDS attached to the SEM. Next, for the Zn penetration depth, 5 arbitrary fields of view (each field of view was 30 μm × 30 μm) were selected in the region near the edge at an SEM magnification of 2000 times, and the position where the interface between the coating layer and the steel material (base steel) was near the center of the field of view was observed. From the element distribution image of Zn measured by SEM-EDS, the maximum Zn penetration depth in the field of view was defined as the "Zn penetration depth." For the depth of the internal oxide layer, one location was selected in the region near the edge, and from there, a total of 10 observation areas (each field of view was 30 μm × 30 μm) were selected at appropriate measurement intervals. The 10 observation regions may overlap, but the total length L0 of the width of the steel plate to be observed is set to 100 μm, and the depth to be measured is set to the region from the surface of the steel plate to 30 μm. The distance from the surface of the steel plate to the furthest position where any particulate oxide exists is defined as the "depth of the internal oxide layer" (Rn). The "depth of the internal oxide layer," the "Zn penetration depth," and their difference ("Zn penetration depth - depth of the internal oxide layer") are shown in Tables 1 and 2.

[0107] (Evaluation of LME resistance of spot welds) After completing the above welding for each evaluation sample of each steel welded component specimen, the cross section of the spot weld (nugget and pressure weld) and the part including the steel material was observed with an optical microscope (for example, the part shown in Figure 1). The length of the LME crack that occurred in the weld cross section in the observed image was measured and evaluated according to the following criteria. The results are shown in Tables 1 and 2. Rating AAA: No LME cracks Rating AA: LME crack length 0μm to 100μm Rating A: LME crack length over 100μm to 500μm Rating B: LME crack length over 500 μm

[0108] [Table 1]

[0109] [Table 2]

[0110] For samples No. 1 to 21 and 36 to 43 in Table 1, in the region 10 to 300 μm from the end of the pressure welded part of the spot weld, the difference between the Zn penetration depth of Zn from the Zn-based coating layer into the steel material and the depth of the internal oxide layer formed in the steel material was in the range of 0.1 μm or more, so that the samples had high LME resistance and also had high strength. Samples No. 22 to 35 and 44 to 50 in Table 2 are comparative examples outside the scope of the present invention. Sample No. 22 had an insufficient amount of C, and was unable to obtain sufficient strength. Sample No. 23 had a low dew point during annealing, so fine internal oxides were not sufficiently formed, and fine ferrite phases were not sufficiently formed, so that the difference between the Zn penetration depth and the depth of the internal oxide layer was not sufficiently large, and therefore high LME resistance was not obtained. Sample No. 24 had a high dew point during annealing, so that an outer oxide layer was formed on the surface of the steel sheet, and a coating layer was not obtained. In sample No. 25, the holding temperature during annealing was high, so that the internal oxides in the ferrite phase coarsened, and the desired fine internal oxides could not be obtained. In addition, the ferrite phase also grew, and the desired fine ferrite phase could not be obtained. As a result, the difference between the Zn penetration depth and the depth of the internal oxide layer was not large enough, and high LME resistance was not obtained. In sample No. 26, the holding temperature during annealing was low, so that the fine internal oxides were not sufficiently formed, and the pinning effect of the internal oxide on the ferrite phase grain boundary was insufficient, so the ferrite phase coarsened, and the difference between the Zn penetration depth and the depth of the internal oxide layer was not large enough, and high LME resistance was not obtained. In addition, sufficient strength was not obtained. In sample No. 27, brush grinding treatment was not performed before annealing, so that the fine internal oxides were not sufficiently formed, and the difference between the Zn penetration depth and the depth of the internal oxide layer was not large enough, and high LME resistance was not obtained. In sample No. 28, the holding time during annealing was long, which caused the internal oxides in the ferrite phase to coarsen, and a sufficient amount of fine internal oxides was not formed. In addition, the pinning effect of the fine internal oxides on the ferrite phase grain boundaries was insufficient, so the desired ferrite phase was not formed and the difference between the Zn penetration depth and the depth of the internal oxide layer was not large enough, so high LME resistance was not obtained. Samples No. 29 and 31 had excessive Si and Mn contents, respectively, so an outer oxide layer was formed on the surface of the steel sheet and no coating layer was obtained.In the samples No. 30 and No. 32, the Si content and Mn content were insufficient, respectively, and fine ferrite phase was not sufficiently formed, and the difference between the Zn penetration depth and the depth of the internal oxide layer was not large enough, and high LME resistance was not obtained. In the sample No. 33, the Al content was excessive, and an outer oxide layer was formed on the surface of the steel sheet, and a coating layer was not obtained. In the sample No. 34, the Al content was insufficient, and fine inner oxide in the ferrite phase was not sufficiently formed, and the difference between the Zn penetration depth and the depth of the internal oxide layer was not large enough, and high LME resistance was not obtained. In the sample No. 35, an outer oxide layer was formed on the surface of the steel sheet and a coating layer was not obtained, using 4 vol% H2 with a dew point of 0.1°C as the humidified atmosphere during annealing. In the sample No. 44, the cold-rolled steel sheet was not pickled, and the inner oxide layer formed by rolling was left, and then brush grinding and heat treatment were performed under the conditions shown in Table 1. The depth of the internal oxide layer of the cold-rolled steel sheet was 0.8 μm, so the fine ferrite phase and its internal oxide were not sufficiently formed, and high LME resistance was not obtained. In sample No. 45, the holding time during annealing was long, so the internal oxide in the ferrite phase coarsened, and fine internal oxide was not generated in a sufficient amount. In addition, the pinning effect of the fine internal oxide on the ferrite phase grain boundary was insufficient, so the desired ferrite phase was not formed, and the difference between the Zn penetration depth and the depth of the internal oxide layer was not large enough, and high LME resistance was not obtained. In sample No. 46, the dew point during annealing was low, so the internal oxide layer was not sufficiently formed, and the difference between the Zn penetration depth and the depth of the internal oxide layer was not large enough, and high LME resistance was not obtained. In sample No. 47, the dew point during annealing was high, so an outer oxide layer was formed on the surface of the steel sheet, and a coating layer was not obtained. For sample No. 48, a humidified atmosphere with a dew point of 11°C and 7 vol% H2 was used during annealing, and an outer oxide layer was formed, a fine inner oxide layer was not formed sufficiently, and the difference between the Zn penetration depth and the depth of the inner oxide layer was not large enough, resulting in insufficient LME resistance.For sample No. 49, a humidified atmosphere with a dew point of 11°C and 22 vol% H2 was used during annealing, and the inner oxide layer was not formed sufficiently, resulting in insufficient pinning effect of the inner oxide on the ferrite grain boundary, resulting in coarsening of the ferrite phase, and the difference between the Zn penetration depth and the depth of the inner oxide layer was not large enough, resulting in insufficient LME resistance.Sample No. 50 was not humidified during heating, but was humidified only during isothermal heating. As a result, a sufficiently large amount of fine internal oxides was not generated, and the difference between the Zn penetration depth and the depth of the internal oxide layer was not large enough, so that high LME resistance was not obtained.

[0111] In the examples of the invention, it was confirmed that in a region 10 to 300 μm from the end of the pressure welded portion of the spot weld, the difference between the Zn penetration depth of Zn from the Zn-based plating layer into the steel material and the depth of the internal oxide layer formed in the steel material was within a range of 0.1 to 10.0 μm. Therefore, high LME resistance was obtained. In addition, high strength was also obtained. On the other hand, in the comparative examples, the difference between the Zn penetration depth and the depth of the internal oxide layer was not large enough, and therefore at least one of the following was confirmed: poor LME resistance, no plating layer was obtained, or high strength was not obtained. [Industrial Applicability]

[0112] According to the present invention, it is possible to provide a steel welded component having high LME resistance at spot welds, and the steel welded component can be suitably used for applications such as automobiles and building materials, particularly for automobiles, and is expected to exhibit high LME resistance and have a long life as an automobile steel welded component. Therefore, the present invention can be said to be an invention of extremely high industrial value. [Explanation of symbols]

[0113] 1 Steel welded components 11 Zn-based plated steel 21 Spot welds 23 Nugget Section 25 Pressure Welding Part 27 End of insulation displacement part 28 Non-jointed part (separation part) 29 Plating layer in the area near the edge (area 10 to 300 μm from the edge of the pressure weld) 41 Steel plate 44 Base steel (steel crystal phase) 45 Granular oxide

Claims

1. A steel welded member in which a plurality of Zn-based plated steel materials having a Zn-based plated layer on a surface of the steel material are joined via at least one spot weld, At least one of the Zn-based plated steel materials has a tensile strength of 780 MPa or more, The steel material comprises, in mass%, C: 0.05-0.40%, Si: 0.2-3.0%, Mn: 0.1 to 5.0%, sol. Al: 0.4 to 1.50%, P: 0.0300% or less, S: 0.0300% or less, N: 0.0100% or less, B: 0 to 0.010%, Ti: 0 to 0.150%, Nb: 0 to 0.150%, V: 0 to 0.150%, Cr: 0-2.00%, Ni: 0-2.00%, Cu: 0-2.00%, Mo: 0-1.00%, W: 0-1.00%, Ca: 0-0.100%, Mg: 0-0.100%, Zr: 0 to 0.100%, Hf: 0 to 0.100%, and REM: 0 to 0.100%, with the balance being Fe and impurities; A steel welded member, characterized in that in a region 10 to 300 μm from an end of a pressure welded portion of the spot weld, a difference obtained by subtracting a depth of an internal oxide layer formed in the steel material from a Zn penetration depth of Zn from the Zn-based plating layer into the steel material is within a range of 0.1 to 10.0 μm.

2. 2. The steel welded component according to claim 1, wherein the difference between the Zn penetration depth and the depth of the internal oxide layer is in the range of 1.5 to 10.0 μm.

3. In a region of more than 1000 μm from the end of the pressure welded portion of the spot weld, 3. The steel welded member according to claim 1, wherein the Zn-based plating layer has a composition, in mass%, of Al: 0.3 to 1.5%, with the balance being Zn and impurities.

4. In a region of more than 1000 μm from the end of the pressure welded portion of the spot weld, 3. The steel welded member according to claim 1, wherein the Zn-based plating layer has a component composition containing, in mass%, Al: 0 to less than 0.1%, with the balance being Zn and impurities.

Citation Information

Patent Citations

  • Method of improving corrosion resistance, tensile strength and fatigue strength of joint obtained by applying spot welding to high strength plated steel sheet

    JP2005103608A

  • Spot welding method

    JP2017047475A

  • Spot welding member

    JP2020179413A

  • Galvanized steel sheet with high resistance spot weldability

    JP2020524743A

  • Alloyed hot-dip galvanized steel plate and manufacturing method therefor

    WO2014102901A1